The effects of cold-water immersion on power output and heart rate in elite cyclists - Schniepp, J.; Campbell, T. S.; Powell, K. L.; Pincivero, D. M. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this study was to examine the effects of cold-water immersion on power output, heart rate, and time to peak power in 10 well-trained cyclists. The Compu-trainer Professional Model 8001 computerized stationary trainer was used to evaluate maximum power, average power, and time to peak power during a simulated cycling sprint. The heart rate was measured using a Polar heart rate monitor. Subjects performed 2 maximum-effort sprints (for approximately 30 seconds) separated by either an experimental condition (15 minutes of cold-water immersion at 12 degrees C up to the level of the iliac crest) or a control condition (15 minutes of quiet sitting). All subjects participated under both control and experimental conditions in a counterbalanced design in which 5 subjects performed the experimental condition first and the other 5 subjects performed the control condition first. Each condition was separated by at least 2 days. The time to peak power was not different between the 2 conditions. Maximum and average powers declined by 13.7 and 9.5% for the experimental condition but only by 4.7 and 2.3% for the control condition, respectively. The results also demonstrated a significantly greater decline in maximum heart rate after cold-water immersion (8.1%) than under the control condition (2.4%). Average heart rate showed a decrease of 4.2% under the experimental condition, as compared with an increase of 1.5% under the control condition. The major findings of this study suggest that a relatively brief period of cold-water immersion can manifest significant physiological effects that can impair cycling performance.